PENDAPATAN USAHATANI PADI SAWAH DI DESA KAYUUWI KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA - Mundung, Thesalonika; Kapantow, Gene Henfried Meyer; Timban, Jean Fanny Junita (AGRI-SOSIOEKONOMI, 2022)
This study aims to analyze the income of lowland rice farming in Kayuuwi Village, West Kawangkoan District, Minahasa Regency. This research was carried out within 4 months, from September to December 2021. The data collected in this study were primary data obtained from direct interviews with members of lowland rice farmer groups using a questionnaire. Secondary data were obtained from the Kayuuwi Village Office, as well as data taken from agencies related to this research, namely BP3K, West Kawangkoan District, and West Kawangkoan District Office. Sampling was done by means of a simple random sample (simple random sampling) as many as 29 samples. The results showed that the income from respondent farmers with a land area of 9.49 ha was Rp. 152,734,985, - then the average income of farmers was the result of the total income of Rp. 152,734,985, - minus the total cost of Rp. 97,938,284, - was Rp. 54,796. 701, - with an average of Rp. 5,774,152, - per hectare. Lowland rice farming in Kayuwi Village has the feasibility of farming because it is relatively profitable, with an R/C value of 1.55.